Religious Tolerance in the Constitution and Guarantees for the Protection of Human Rights (Jurnal Scientia Indonesia, 2022)
Protection of human rights is an absolute guarantee that must be fulfilled by the rule of law.  Article 1 Paragraph 3 of the 1945 Constitution of the Republic of Indonesia mandates that " The State of Indonesia shall be a state based on the rule of law. " it shows Indonesia recognizes and protects human rights, one of which is the right or freedom to believe in a particular religion. The purpose of this study is to figure out how the regulation of religious tolerance ruled in the Constitution of the Republic of Indonesia/ Undang-Undang Dasar Negara Republik Indonesia Tahun 1945. This research is descriptive research by describing, and analyzing, the issues of tolerance and human rights. The approach used is a legal approach by tracing all relevant laws and regulations. The data collection technique used in this study is a library research technique, which is a data collection technique by reviewing journals, laws and regulations, and other related materials related to the regulation of religious tolerance in Indonesia. That guarantees for the protection of human rights as mandated by the constitution can create religious tolerance among people of different religions in the plurality of Indonesian society. Religious tolerance in Indonesia will create inter-religious harmony to maintain peace, order, tranquility, and the prosperity of the people, nation and state of Indonesia.